Diálogo, contextualização dos saberes e autonomia em Paulo Freire e a semipresencialidade na Educação Superior - Bohrz, Rafaela (2017)
In designing the individuals liberation by moorings oppression in traditional education, the education for critical consciousness, by Freire, propose a pedagogical act anchored in teacherlearners-object of knowledge, which a teacher is rarely seen as knowledge mediator, because the object of knowledge is transformed by student. Thus, teachers and learners are strategic subjects in the educational process, who search through dialogue, reflection and critical insertion in the reality, a transformation of your context, rendering, accordingly, the education into a permanent and emancipatory process. In this sense, such knowledges about Freire’s pedagogy become necessary in Distance Learning in order that it can also produce an education for freedom. On the basis of these theoretical and methodological principles for education, the research exposed in this dissertation investigates the presence of Freire's evidences referring to dialogue, autonomy and knowledge contextualization in educational practices of blended disciplines in one higher education institution, located in Passo Fundo/RS. With the purpose to answer this goal, was performed an initial literature review related of Freire theory and Distance Learning; a selection of sample (four disciplines of distinct courses, with different credits numbers and tasks carried); an application of three instruments, checklists to identify Freire’s categories on blended disciplines, systematic observation/non-participation, which allow the logical-conceptual categories approach in collective and individual activities in Moodle platform, and an analysis of founded evidences so that ascertain the significance of Freire's theory in comprehension and successful experiences in Distance Learning. While emphasize Freire's categories of blended disciplines, this research showed some difficulties in relation to choice and development activity by teachers, participants in the sample, than report that dialogue implementation, autonomy and knowledge contextualization in educational practices did not occur in full form and the modification of traditional education, using blended learning and Information and Communication Technology, requires a new perspective, planning and subject innovation involved in education process.